ON THE ISSUE OF THE FEATURES OF A CORPORATE-LEGAL STATUS OF A SHARE-HOLDER - Yu. V. Akhmetova (Russian Journal of Economics and Law)
The article studies the features of a legal status of a share-holder as a subject of corporate relations. The author analyzes approaches elaborated by science and court practice referring to the category of a share-holder's legal status; defines the general and specific elements of a share-holder's legal status. Basing on the conclusions, it is proposed to use the definition "corporate-legal status" as a special legal status of a share-holder.